Association between plasma uric acid and insulin resistance in type 2 diabetes: A Mendelian randomization analysis. (January 2021) - Hu, Xueting; Rong, Shuang; Wang, Qiang; Sun, Taoping; Bao, Wei; Chen, Liangkai; Liu, Liegang
Abstract: Objective: Circulating uric acid levels were associated with insulin resistance, but the causality is unclear. We aimed to investigate the association between plasma uric acid and insulin resistance in newly diagnosed type 2 diabetes (T2D). Methods: We enrolled 1, 938 patients who underwent a 75-g oral glucose tolerance test. Insulin resistance was estimated based on the homeostatic model assessment index (HOMA2-IR) and the Matsuda index. Uric acid was measured in fasting plasma by uricase-peroxidase method. We genotyped single nucleotide polymorphisms (SNPs) that were recently identified as top hits in genome-wide association studies of uric acid levels. A weighted genetic risk score (wGRS) was calculated based on the associations between selected SNPs and uric acid levels. Results: The adjusted β coefficients for Ln-transformed Matsuda index and HOMA2-IR per 1 mg/dL uric acid increment were −0.070 (95%CI: −0.089, −0.052) and 0.057 (95%CI: 0.039, 0.075). These associations were more pronounced among women than men. In Mendelian randomization analysis, the wGRS raised uric acid by 0.225 mg/dL (95%CI: 0.138, 0.312) per SD increase of the score. However, no association was observed between the wGRS and insulin resistance indices whether in men or women. Conclusions: Elevated plasma uric acid was associated with higher risk of insulin resistance, along with observation of gender difference in such association. However, our study does not support a causal role of plasma uric acid on insulin resistance among newly diagnosed T2D patients.